2005
DOI: 10.1111/j.1741-3737.2005.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Families in the Life Course: Interdependency of Roles, Role Configurations, and Pathways

Abstract: Families are central in the unfolding life course. They have both internal and external dynamics that reflect and characterize the modern life span, and a life course perspective has particular utility for understanding the role and implications of families for individuals and society. The purpose of this paper is 3-fold. First, we offer a family life course perspective that delineates core concepts of roles, role configurations, and pathways, specifies the links between them, and highlights the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
205
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(211 citation statements)
references
References 56 publications
2
205
0
4
Order By: Relevance
“…Studies of earlier cohorts found that these pathways were differentiated primarily by the timing of family formation and participation in postsecondary education (Macmillan and Copher, 2005;Osgood et al, 2005;Sandefur et al, 2005). Similar results were found in the present sample of contemporary young adults but with important gender differences.…”
Section: Pathways To Adulthoodmentioning
confidence: 99%
“…Studies of earlier cohorts found that these pathways were differentiated primarily by the timing of family formation and participation in postsecondary education (Macmillan and Copher, 2005;Osgood et al, 2005;Sandefur et al, 2005). Similar results were found in the present sample of contemporary young adults but with important gender differences.…”
Section: Pathways To Adulthoodmentioning
confidence: 99%
“…The family life course perspective pays attention to the interaction between demographic, social and cultural factors that shape family relations and emphasizes the changes in roles and positions in the family and household domain of individuals when they experience life course transitions (Elder 1994;Hareven 1994;Elder et al 2003;MacMillan and Copher 2005). The fact that family members lead 'linked lives' (Elder 1994) also implies that those changing roles both influence and are influenced by other persons connected to the individual experiencing the transition (MacMillan and Copher 2005;Aquilino 1997;Bucx et al 2008). Moreover, life course theories stress the importance of previous life course experiences: they shape and influence decisions and pathways later in the life course (Hareven 1994).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Rejection by the parents fosters a distorted and devaluated self concept and self image for the child. He may feel helpless, inferior and insecure according to Macmillan & Copher (2005) parentally rejected children feel neglected, isolated and alone. They frequently attempt to gain acceptance and positive social relationships through a variety of attention seeking behaviors like temper tantrums, disobedience, lying, stealing etc, as reported by (Kerr, Lopez, Olson & Sameroff, 2004).…”
Section: Familymentioning
confidence: 99%
“…The universal functions of the families are to provide sexual activity to raise children, to provide care, love and nurturing and discipline and to provide a supportive environment to the family. Function is the usage that has evolved from the contribution that an activity or an item makes the whole, the consequence of the activity or item for the system being considered (Macmillan & Copher, 2005). Family functioning includes production activities, such as income generating activities, home making activities, learning activities, regarding social and cultural norms and expectations, education, health and nutrition, social activities, and cultural activities.…”
Section: Familymentioning
confidence: 99%